Peramalan Nilai Tukar Rupiah Terhadap Mata Uang Negara Asia Menggunakan Metode Quantum Neural Network - Iswardani, Putu Risanti; Sudarma, Made; Jasa, Lie (Jurnal Teknologi Elektro, 2021)
Currency is a standardized payment instrument used all around the world. Almost each country has their own currency, and it has a variable value. Asia is one of the biggest continent in the world. Most tourists whom visit Indonesia come from Asia. Thus, that makes the most currency exchanged in Indonesia are currencies from Asia. Currency exchange rate difference between one currency and another affected by several factor. One of those factor is inflation in its country. To overcome that issue, one needs a prediction system that can be used to predict the exchange rate of currencies in the future. Quantum Neural Network is used in this research to predict Indonesian Rupiah exchange rate value to other currency in Asia. Singapore, Hongkong and Japan currencies are particularly used in this research. Results obtained from this research are accuracies. Quantum Neural Network produces 99.78% accuracy on Singapore Dollar to Indonesian Rupiah exchange rate, 99.57% on Hongkong Dollar to Indonesian Rupiah, and 99.60% on Japanese Yen to Indonesian Rupiah.